Evaluation of Cloud-Based Financial Information System in Overcoming Company Liquidity Crisis - Utama, Ahmad Nur Budi; Hidayat, Imam; Mutia, R. Dewi; Rasna, Rasna; Judijanto, Loso (Malikussaleh University, Aceh, Indonesia, 2025)
This study evaluates the effectiveness of cloud-based financial information systems in addressing corporate liquidity crises. It aims to identify how cloud financial systems improve liquidity stability, financial decision-making, and operational efficiency while examining key implementation challenges. A mixed-methods approach was applied, combining quantitative multiple linear regression analysis and qualitative case studies from 10 selected Indonesian companies across various sectors. The study measured key factors, including financial data access speed, accuracy, cash flow prediction, and liquidity management efficiency. The quantitative results show that all independent variables positively and significantly impact corporate liquidity stability (p-value 0.05). Liquidity management efficiency (coefficient = 0.366) had the most potent effect, followed by financial data access (0.347), accuracy and transparency (0.340), and cash flow prediction (0.308). The qualitative findings further validate these results, with companies reporting better financial forecasting, reduced manual errors, and improved decision-making speed. However, key challenges include high implementation costs, cybersecurity risks, and system integration difficulties. Businesses must adopt strategic implementation plans, focusing on enhanced cybersecurity measures, affordable cloud solutions, and team member training programs to maximize cloud financial benefits. SMEs, in particular, require scalable cloud options to mitigate financial and technological constraints. Cloud-based financial systems significantly enhance corporate financial stability and sustainability. Companies that effectively integrate these systems will gain higher financial resilience and competitive advantage in the digital era. However, addressing cost, security, and integration challenges is essential for optimizing cloud technology adoption.